2007
DOI: 10.1253/circj.71.814
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk Attributable to Atrial Fibrillation in Middle-Aged and Elderly People in the Japanese General Population

Abstract: AF affects stroke mortality, cardiovascular mortality and all-cause mortality in the Japanese general population. Careful attention should be paid to persons with AF in order to prevent future cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 22 publications
6
49
1
2
Order By: Relevance
“…19,25,26 The present study focused on PAF, which is different from previous clinical trials. In the present study, total mortality and cardiovascular morbidity rates were remarkably low compared with those in the previous studies, in which most or all patients had persistent AF.…”
Section: Cardiovascular Mortality and Morbidity In Pafmentioning
confidence: 99%
See 1 more Smart Citation
“…19,25,26 The present study focused on PAF, which is different from previous clinical trials. In the present study, total mortality and cardiovascular morbidity rates were remarkably low compared with those in the previous studies, in which most or all patients had persistent AF.…”
Section: Cardiovascular Mortality and Morbidity In Pafmentioning
confidence: 99%
“…18,19 We herein present new data concerning rate and rhythm control strategies in patients with PAF.…”
mentioning
confidence: 99%
“…However, since 2005, several reports have started to address this important issue in Japan. [4][5][6] The first of these studies was NIPPON DATA 80, 4 in which trial fibrillation (AF) is the most common arrhythmia among the developed countries, and its prevalence nearly doubles with each decade of life, increasing by as much as 25% on a lifetime basis. 1 As the population ages, the number of AF patients is predicted to increase.…”
Section: Mortality Rates Of Japanese Af Patientsmentioning
confidence: 99%
“…NIPPON DATA 80 4 reported that approximately 40% of the deaths were not of cardiovascular origin. In the J-TRACE study, 5 approximately 80% of the deaths were classified as "other" (not due to stroke, myocardial infarction, or major bleeding).…”
Section: Af Mortality and Morbidity In Japanmentioning
confidence: 99%
“…4) However, antiarrhythmic drug therapy whose aim is the maintenance of sinus rhythm has prognostic limitations. 5) Recently, in order to correct arrhythmogenic structural remodeling of the atrial muscle, an etiological factor for AF, upstream therapy combining angiotensin-converting enzyme inhibitors (ACEI) and statins with antiarrhythmic agents, has drawn attention.…”
mentioning
confidence: 99%